2012
DOI: 10.1346/ccmn.2012.0600203
|View full text |Cite
|
Sign up to set email alerts
|

Ni Enrichment and Stability of Al-Free Garnierite Solid-Solutions: A Thermodynamic Approach

Abstract: Abstract-Garnierites represent significant Ni ore minerals in the many Ni-laterite deposits worldwide. The occurrence of a variety of garnierite minerals with variable Ni content poses questions about the conditions of their formation. From an aqueous-solution equilibrium thermodynamic point of view, the present study examines the conditions that favor the precipitation of a particular garnierite phase and the mechanism of Ni-enrichment, and gives an explanation to the temporal and spatial succession of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
22
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 29 publications
9
22
0
3
Order By: Relevance
“…It is suggested that the last zone to dry is in the centre of the joint, and there, water precipitates the remaining Si and Mg once Ni is already precipitated as pimelite near the joint boundary, or alternately, Mg-rich silicate could also have precipitated earlier. Pimelite is much more insoluble than Mg-kerolite, thereby explaining why this mineral precipitates first despite a Ni/Mg ratio in water close to 10 −3 ; this process was already described by Galí et al (2012). The process is probably recurrent and repeated several times before reaching a significant volume of precipitated minerals but is limited to joints with a sufficiently low permeability, preventing rapid dissolution and the release of elements into the percolating waters.…”
Section: Physical-chemical Processes Linked To Target-like Ore Formationmentioning
confidence: 80%
“…It is suggested that the last zone to dry is in the centre of the joint, and there, water precipitates the remaining Si and Mg once Ni is already precipitated as pimelite near the joint boundary, or alternately, Mg-rich silicate could also have precipitated earlier. Pimelite is much more insoluble than Mg-kerolite, thereby explaining why this mineral precipitates first despite a Ni/Mg ratio in water close to 10 −3 ; this process was already described by Galí et al (2012). The process is probably recurrent and repeated several times before reaching a significant volume of precipitated minerals but is limited to joints with a sufficiently low permeability, preventing rapid dissolution and the release of elements into the percolating waters.…”
Section: Physical-chemical Processes Linked To Target-like Ore Formationmentioning
confidence: 80%
“…6) were constructed following the procedure of Galí et al (2012) to understand the relative solubility of different phases with respect to the interfacial fluid composition. The figure also lists the respective dissolution reactions shown on the diagrams and corresponding log K values.…”
Section: Phase Relationship and Implication Of A Layered Replacement Rimmentioning
confidence: 99%
“…For Ni-olivine (Ni 2 SiO 4 ), the thermodynamic data was used as reported in Robie et al (1984). In order to calculate the Gibbs free energy change during the Ni-endmember phase dissolution reaction, the Gibbs free energies of formation for dissolved aqueous species were taken from Galí et al (2012) and references therein. The thermodynamic data for Ni-end-member phases are not available for high temperatures and pressures and hence, each diagram was calculated at standard conditions (25°C and 0.1 MPa pressure).…”
Section: Phase Relationship and Implication Of A Layered Replacement Rimmentioning
confidence: 99%
See 1 more Smart Citation
“…Os dados de química mineral de olivinas e serpentinas compilados da bibliografia internacional mostram que as concentrações de NiO apresentados por diversos autores são condizentes com as concentrações destes minerais no ESrg, obtidos nesta pesquisa. Demonstram também que as análises de olivinas realizadas em amostras de depósitos lateríticos de níquel (Gleeson, 2004;Galí, 2012) atingem valores superiores, chegando a níveis de 0,50%, compará-veis ao determinado para as olivinas da Sequência Cerro Mantiqueiras no ESrg.…”
Section: Considerações Finais E Conclusõesunclassified